Test Of the Effectiveness of Tomato (Lycopersicum Esculentum Mill) Fruit Extract Cream on Increasing Elasticity, Sebum and Hydration in White Mouse Skin (Mus Musculus) - Irnawasti Irnawasti; Djamin Katarino; Hendy Million (International Journal of Health and Pharmaceutical (IJHP), 2023)
The skin is the outermost organ that acts as a protector from the external environment both in the ligaments, muscles, and internal organs from exposure to direct sunlight (ultraviolet light) and dehydration, also functions as a sense of taste and touch as well as a defense against pressure and infection. The imbalance between oxidants and antioxidants is influenced by external factors and internal factors that will affect wrinkling and aging of the skin. Tomatoes contain substances such as citrulline, vitamin A, vitamin B2, vitamin B6, vitamin E, vitamin C, and protein, beta-carotene, lycopene, and water. The purpose of this study was to determine the activity of tomato fruit ethanol extract to increase elasticity, sebum and hydration in the skin of male white mice. Cream preparations of tomato fruit ethanol extract were formulated with concentrations of 2.5%, 5%, and 10%. The test was carried out on the skin of male mice for 4 weeks by measuring the levels of elasticity, sebum and hydration. The results of phytochemical screening of extracts contained flavonoids, saponins, steroids, triterpenoids, and glycosides. The measurement results in the fourth week of each group of cream preparations showed an increase in the levels of elasticity, sebum and hydration and was significantly different from the blank group (p<0.05) and the highest increase occurred in cream with 10% tomato extract concentration. The results of this study indicate that the preparation of tomato fruit ethanol extract cream can increase the elasticity, sebum and hydration levels of the skin.